Uma ontologia para a descrição da semântica da IMML - Lira, Heremita Brasileiro (2006)
This work presents an ontology to describe the semantics of IMML (Interactive Message Modeling Language) an XML-based User Interface Description Language. The ontology presents the description of all IMML elements including a natural language description and semantic rules and relationships. The ontology is implemented in OWL-DL, a standard language to ontology description that is recommended by W3C. Our main goal is to describe the semantic using languages and tools that can be processed by computers. As a consequence, we develop tools to the validation of a user interface specification and also to present the semantic description in different views